Muscular Dystrophy Research Updates and Therapeutic Strategies - Gaina, Gisela (IntechOpen, 2020)
Muscular Dystrophy - Research Update and Therapeutic Strategies is for students, researchers, and clinicians interested in muscular dystrophies who want to improve their knowledge of these complex genetic diseases. The book includes information about the genetics of various types of muscular dystrophies as well as explores new and current therapeutic strategies that aim to ameliorate symptoms and improve patients' quality of life and life expectancy. In addition, this book reviews information on current clinical trials for muscular dystrophies and presents a framework for what to consider during the design of these trials.